2018
DOI: 10.1136/thoraxjnl-2017-210408
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal profiling of the lung microbiome in the AERIS study demonstrates repeatability of bacterial and eosinophilic COPD exacerbations

Abstract: BackgroundAlterations in the composition of the lung microbiome associated with adverse clinical outcomes, known as dysbiosis, have been implicated with disease severity and exacerbations in COPD.ObjectiveTo characterise longitudinal changes in the lung microbiome in the AERIS study (Acute Exacerbation and Respiratory InfectionS in COPD) and their relationship with associated COPD outcomes.MethodsWe surveyed 584 sputum samples from 101 patients with COPD to analyse the lung microbiome at both stable and exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
252
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(285 citation statements)
references
References 37 publications
30
252
2
1
Order By: Relevance
“…This microbiota composition during bacterial exacerbations was characterized by a higher relative abundance of members of either the Haemophilus or Moraxella genera . Similar findings were reported in the AERIS study; a second large longitudinal study in COPD …”
Section: Respiratory Microbiome As a Clinically Informative Indicatorsupporting
confidence: 83%
See 2 more Smart Citations
“…This microbiota composition during bacterial exacerbations was characterized by a higher relative abundance of members of either the Haemophilus or Moraxella genera . Similar findings were reported in the AERIS study; a second large longitudinal study in COPD …”
Section: Respiratory Microbiome As a Clinically Informative Indicatorsupporting
confidence: 83%
“…Patients who suffer exacerbations more frequently than would be predicted based on established risk factors are at a higher risk of serious complications . Results from the AERIS study showed that eosinophilic and bacterial exacerbations in COPD were more likely to be recurring, compared to viral exacerbations . Pre‐exacerbation microbiota diversity was also found to be lower in those experiencing more frequent exacerbations .…”
Section: Respiratory Microbiome As a Clinically Informative Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,32 However, it cannot simply be assumed that thresholds for pharmacodynamic re- 35,36 and eosinophilic respiratory exacerbations portend a higher likelihood of subsequent eosinophilic exacerbation. 37 Taken together, these data suggest that high blood eosinophils could be taken as a biomarker of eosinophilic asthma, and by corollary a biomarker of response to treatments targeted at eosinophilic asthma. Our data demonstrated an obvious divergence of long-term disease trajectory at the threshold BEC of 1.2 × 10 9 cells/L, suggesting that this group may exhibit the severe eosinophilic phenotype characterized by frequent exacerbations.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies utilizing specific bacterial 13S-rRNA screening showed bacterial colonization, including colonization of quinolone- or GRNX-sensitive bacteria, in both upper and lower airways of patients with asthma and COPD [22-25]. Exacerbation of CRDs were also related to microbial dysbiosis in lower airways, suggesting antibiotics may play a role in these settings [24, 26].…”
Section: Discussionmentioning
confidence: 99%